Results of the lung and colorectal cancer screening study in China: a feasibility, randomised controlled trial. Issue 1 (October 2019) - Li, Jiang; Hu, Ping; Shi, Jufang; Taylor, Martina; Li, Ni; Ren, Jiansong; Chen, Hongda; Liao, Xianzhen; Liu, Yuqin; Du, Lingbin; Pinsky, Paul; Prorok, Philip; et al.
Abstract: Background: China has not yet developed national guidelines for lung and colorectal cancer screening, and needs scientific evidence from the Chinese population for making policy. The aim of this study was to obtain compliance information to design a large-scale randomised lung and colorectal cancer screening trial in China. Methods: This multicentre, open label, pilot randomised trial was done at 33 community health-care centres and three hospitals in Haining (Zhejiang province), Changsha (Hunan province), and Lanzhou (Gansu province). Eligibility criteria included participants aged between 50 and 74 years, current smokers with a history of at least 30 pack-years, and passive smokers. Exclusion criteria included participation in another trial, history of lung or colorectal cancer, or evidence of previous cancer treatment. Participants were randomly allocated (1:1:1) using a predefined web-based system to: group 1, annual low-dose CT (LDCT) plus a baseline colonoscopy; group 2, biannual LDCT plus annual fecal immunochemical test (FIT); and group 3, annual fecal FIT plus septin-9 blood test. The primary outcomes of the study included the annual compliance and incidence of lung and colorectum cancer. This study was approved by the Ethical Committee of the Cancer Hospital, Chinese Academy of Medical Sciences, and registered in the Chinese Clinical Trial Registry, number ChiCTR-IOR-15007160. Findings: Between Aug 12, 2014, and June 30, 2017, 2696 participants were randomly assigned to three screening groups. Demographics and smoking history were similar across the three groups. Compliance for annual LDCT in group 1 was 86·8% (777 of 895 participants) at baseline, 69·0% (614 of 890) at the first round (T1), and 70·7% (626 of 885) at the second round (T2). Compliance for colonoscopy in group 1 was 56·4% (504 of 894). In group 2, compliance for biannual LDCT in group 2 was 91·9% (829 of 902) at baseline and 66·6% (595 of 894) at T2; compliance for annual FIT was 91·6% (826 of 902) at baseline, 79·9% (716 of 896) at T1, and 65·8% (588 of 894) at T2. The compliance rate of annual Septin-9 in group 3 was 91·0% (819 of 900) at the baseline, 68·7% (618 of 899) at T1, and 80·8% (725 of 897) at T2; and of annual FIT was 89·2% (803 of 900), 72·3% (650 of 899), and 78·8% (707 of 897), respectively. During the follow-up (until Dec 31, 2017), 13 lung cancer cases were confirmed in groups 1 and 2, and one colorectal cancer case in group 1. Three participants died of lung cancer and 14 died of other causes. Interpretation: In this pilot study, the feasibility study retention was established in a Chinese population and has now been adapted to a large-scale, randomised controlled trial that will determine whether to implement a nationwide screening programme for lung cancer, colorectal cancer, or both, in China. Funding: Cancer Hospital, Chinese Academy of Medical Sciences.